Acculturation is Associated With Higher VO(2max) in Overweight Hispanic Children - Crespo, Noé C. (2006)
Acculturation has been implicated to be associated with physical activity (PA) behaviors in adults; little is known, however, with respect to the pediatric population. The purpose of this study was to determine whether cardiorespiratory fitness (VO(2max)) and/or PA were associated with acculturation status in overweight Hispanic children. In a sample of 144 children 8–13 years old, acculturation status was determined by place of birth: foreign born (n = 17), 1st generation (n = 101), or 2nd/3rd generation (n = 26), and by questionnaire: less assimilated (n = 76) or more assimilated (n = 34). VO(2max) was measured using a treadmill protocol, PA was assessed by questionnaire, and body composition by DEXA. ANOVA and ANCOVA were used to determine unadjusted and adjusted group differences, respectively. After adjusting for covariates, the 2nd/3rd generation group had significantly higher VO(2max) compared with the 1st generation group: 2.26 ± 0.20 L/min vs. 2.15 ± 0.19 L/min, p = .03. No differences were noted for PA, however. Acculturation to the U.S. is associated with higher VO(2max) in overweight Hispanic children. Longitudinal analyses are needed to determine whether these fitness differences confer protective health effects in this at-risk population.